Clinical genomics practical applications in adult patient care (Mcgraw-Hill Education/Medical, 2014)
The first book on the clinical application of genetics in primary care medicine, Clinical Genomics focuses on the everyday application of genetic assessment and its diagnostic, therapeutic, and preventive implications in clinical practice. Unlike traditional textbooks on medical genetics and dysmorphology, this is a clinical reference that covers many of the common diseases seen in everyday medical practice. Features: endorsed by the American College of Physicians; addresses the genetic basis of common chronic diseases, not just the classic diseases of dysmorphology.